Expressive speech acts in the character of nakano nino in anime gotoubun no hanayome season 1 - Sudarma, I Nyoman; Bimantara, Kadek Danu; Yudi Darma Laksana, Komang Tri; Hermawan, Gede Satya (Journal of Language Education Studies and Applied Linguistics, 2025)
This research focuses on expressive speech acts in anime Gotoubun no Hanayome season 1. The aim of this research is to describe the forms of expressive speech acts uttered by the character Nakano Nino in the anime Gotoubun no Hanayome season 1. This research is a type of qualitative descriptive research with a descriptive approach. Data selection was carried out using the theory of John Searle (1979). Data was obtained using the note-taking technique and analyzed using the pragmatic matching method. The results of the research showed that there were 21 data of expressive speech acts, with details of 2 speech data with the meaning of sarcasm, 2 data of speech with the meaning of apologizing, 7 data of speech with the meaning of annoyance, 6 data of speech with the meaning of worry, 3 data of speech with the meaning of praising, 1 data of speech with the meaning of speech with the meaning of complaining. Based on the data found, it is known that the most frequently found data is data with the meaning of expressive speech acts of worry.